Development of compound rubber formula for electron beam vulcanization - bhumirabiab, pantila; Pinprayoon, Orawan; Buasuwan, Nichapa; Hemvichian, Kasinee (Bulletin of Applied Sciences, 2022)
The electron beam (E-Beam) vulcanization system is a high-speed vulcanization technique, which offers products with better homogeneity than those obtained from sulfur vulcanization system. In addition, E-Beam vulcanization requires less chemicals than sulfur vulcanization, thus leaving fewer chemical residues and therefore making it an environmentally friendly process. In this study, Standard Thai Rubber (STR) were used to develop rubber compound formulae for electron beam vulcanization. Two types of sensitizer; n-Butyl acrylate (n-BA) and trimethylolpropane trimethacrylate (TMPT) along with their varied amount (3 and 5 phr) were studied and compared to the physical properties (hardness, tensile strength, elongation at break and tension set) of the rubber sheets vulcanized with conventional sulfur system. The study of the optimum dose for electron beam irradiation for rubber vulcanization was carried out using an electron beam accelerator with accelerated energy of 10 million electron volts (MeV) at four different doses: 50 kGy, 100 kGy, 150 kGy and 200 kGy. From this study, it was found that the formulation containing 5 phr TMPT sensitizer, vulcanized with the electron beam at 200 kGy was suitable for vulcanizing rubber products which require low tension set. However, the physical properties of the rubber obtained from this study were slightly lower than those prepared from sulfur-vulcanized system.